Learning Poser 8 - Pubrick, Steve (Infinite Skills, 2010)
In this Poser training video for Poser 8 and Poser Pro 2010, Steve Purbrick takes you through the ins and outs of learning how to use this powerful program. Poser 8 is the latest offering from Smith Micro, and in addition to learning this powerful program, Steve will teach you about specific Poser Pro 2010 functions as well. This Poser 8 - Pro 2010 Tutorial starts at the basics, with a tour interface, but quickly gets into applied learning, covering important topics from working with the various pallets offered in Poser, posing figures, growing hair, clothing your figures, working with props, animating figures, rendering and even goes into using Python scripting with Poser. At the conclusion of this Poser training title, you will be fully capable of creating figures, animating and rendering video in Poser 8 and Poser 2010 and fully versed in the use of the tools provided in this powerful program. Working files are included with the training to allow you to work alongside of the author.